2005
DOI: 10.1110/ps.041255905
|View full text |Cite
|
Sign up to set email alerts
|

Helix periodicity, topology, and dynamics of membrane‐associated α‐Synuclein

Abstract: The protein ␣-Synuclein (aS) is a synaptic vesicle-associated regulator of synaptic strength and dopamine homeostasis with a pathological role in Parkinson's disease. The normal function of aS depends on a membrane-associated conformation that is adopted upon binding to negatively charged lipid surfaces. Previously we found that the membrane-binding domain of aS is helical and suggested that it may exhibit an unusual structural periodicity. Here we present a study of the periodicity, topology, and dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
204
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(224 citation statements)
references
References 55 publications
19
204
0
1
Order By: Relevance
“…While the interaction of α-Syn with the membrane initially induces an α-helical rich structure, 7 here it was observed that in the absence of cellular partners α-Syn self-aggregates on the bilayer at sub-physiological concentrations (Fig. 2).…”
Section: α-Syn Aggregates On Membranesmentioning
confidence: 52%
“…While the interaction of α-Syn with the membrane initially induces an α-helical rich structure, 7 here it was observed that in the absence of cellular partners α-Syn self-aggregates on the bilayer at sub-physiological concentrations (Fig. 2).…”
Section: α-Syn Aggregates On Membranesmentioning
confidence: 52%
“…Although the protein has little structure, it does gain some helical content in the N-terminus when associated with the membrane (2). Its normal role in the cell remains unclear but like a number of other proteins with poorly defined cellular roles, it is mostly known for its association with neurodegenerative diseases.…”
Section: Alpha-synuclein and Neurotoxicitymentioning
confidence: 99%
“…1) is a 140 amino-acid, intrinsically-disordered protein associated with Parkinson's disease and other neurodegenerative disorders [1][2][3][4][5][6][7][8] whose function is hypothesized to involve its interaction with membranes. [8][9][10][11][12] The protein binds lipids and anionic detergents through the seven imperfect, cationic, 11-amino acid repeats located in its N-terminal and hydrophobic regions.…”
mentioning
confidence: 99%
“…1) is a 140 amino-acid, intrinsically-disordered protein associated with Parkinson's disease and other neurodegenerative disorders [1][2][3][4][5][6][7][8] whose function is hypothesized to involve its interaction with membranes. [8][9][10][11][12] The protein binds lipids and anionic detergents through the seven imperfect, cationic, 11-amino acid repeats located in its N-terminal and hydrophobic regions. [6][7][8][13][14][15][16][17][18][19][20] Electron paramagnetic resonance (EPR) data on its complex with small unilamellar vesicles (SUVs) suggest that the first $100 residues of the monomeric protein adopt an a-helical conformation that lies on the membrane surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation